The outcome of early rehabilitation therapy for the patient after percutaneous coronary intervention: a systematic review and meta-analysis - Pande Made Dwi Budiarta; Adhyasta Nata Prawira S; Citra Wulandari Sofyan; Putu Topan Bagaskara (DiscoverSys Inc., 2022)
Background: Acute myocardial infarction (AMI) is one of the leading causes of mortality, morbidity and physical disability worldwide. The chief treatment for AMI is primary percutaneous coronary intervention (PCI). However, the effectiveness of early rehabilitation therapy after PCI patients still lacks documentation. Therefore, a meta-analysis has assessed the patient's outcome of early rehabilitation therapy after PCI. Methods: The searching protocol was carried out using several databases, such as PubMed, ScienceDirect, and Google Scholar, to identify relevant topics in June 2022. This study used the Preferred Reporting Items for Systematic Review and Meta-Analysis 2020 (PRISMA) guidelines. Result: There were nine studies included in this systematic review and meta-analysis. All of the reviewed studies were written in English. Most of the included studies were carried out in China. Most of the included studies were carried out in China. The mean age of the patient were all above 18 years. The total participants were 858 patients with PCI. There was a significant difference in 6-minute walk distance (MD = 85.64; 95% CI = 78.68–92.60; p < 0.01); left ventricle ejection fraction (LVEF) (MD = 5.97; 95% CI = 5.30–6.63; p < 0.01) and body mass index (BMI) score score (MD = 1.43; 95% CI = 0.86–2.00; p < 0.01) between groups in overall analysis. Conclusion: Early rehabilitation in patients with PCI has better outcomes (6-minutes walk distances, LVEF, and BMI score) than in the control group.